2021
DOI: 10.1177/1362361321989221
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural perspectives on the meaning of family quality of life: Comparing Korean immigrant families and Canadian families of children with autism spectrum disorder

Abstract: This study sought to examine and compare conceptualizations and descriptions of family quality of life, from the perspectives of Korean immigrant and Canadian families of children with autism spectrum disorder. Thematic analysis of semi-structured interviews from 13 Korean immigrant parents and 12 Canadian parents of children with autism living in BC, Canada was conducted. For Korean immigrant families, three themes were identified: family cohesiveness, value orientation, and acceptance from society. For Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…They are able to draw strength from various areas and appreciate the individual talents and sense of fulfillment and joy their child brings to their families. This finding is consistent with previous research revealing positive aspects of caregiving and improvements in family functioning for Korean parents raising autistic children (Cho et al, 2000; Fong et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They are able to draw strength from various areas and appreciate the individual talents and sense of fulfillment and joy their child brings to their families. This finding is consistent with previous research revealing positive aspects of caregiving and improvements in family functioning for Korean parents raising autistic children (Cho et al, 2000; Fong et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Families of autistic children report a number of strengths and challenges across the lifespan. Strengths reported include greater closeness among family members, positive relationships between siblings, personal growth, and improved marital relationships (Fong et al, 2021; Mount & Dillon, 2014; Orsmond et al, 2009; Phelps et al, 2009; Rivers & Stoneman, 2003). Families also report a number of challenges raising their autistic child due to the nature and complexity of their child’s social, behavioral, physical, and medical needs (Estes et al, 2013).…”
mentioning
confidence: 99%
“…FQoL is therefore one of the main outcome measures of services and the provision of family support for people with intellectual disabilities [7,9,13]. Guidance from family members is helpful for individuals with disabilities [14][15][16][17]. In this sense, in the past two decades, the FQoL concept received greater attention for its development and utilization [9,18], especially in the field of disability studies [19,20].…”
Section: Zuna Et Al Four Combined Concepts Changed To Practices Of In...mentioning
confidence: 99%
“…Though families and caregivers of autistic children report many positive outcomes and enhanced quality of life ( Fong, Gardiner, & Iarocci, 2021 ), various social, systemic, and environmental barriers exist that place them at greater risk for stress and mental health problems ( Shakespeare & Watson, 2001 ). Research has shown that caregivers of autistic children report higher levels of stress compared to parents of typically developing (TD) children and children with other developmental disabilities ( Hayes & Watson, 2013 ).…”
Section: Coping In Parents Of Autistic Childrenmentioning
confidence: 99%